Biochemistry - Champe, Pamela C. ; Harvey, Richard A. ; Ferrier, Denise R. (New Delhi Lippincott Williams & Wilkins, 2009)
Thoroughly updated for its Fifth Edition, Lippincott's Illustrated Reviews: Biochemistry enables students to quickly review and assimilate large amounts of complex information through powerful visual resources essential to mastery of difficult biochemical concepts. Its signature outline format, full-color illustrations, end-of-chapter summaries, and USMLE-style review questions make it one of the most user-friendly books in the field. New features include case studies for each chapter and expanded coverage of molecular biology. A companion website offers fully searchable online text and additional USMLE-style questions for students and an image bank for faculty.
Include Index
Keywords: Clinical biochemistry